1995
DOI: 10.1016/0092-8674(95)90354-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific deficit of the ON response in visual transmission by targeted disruption of the mGIuR6 gene

Abstract: Taking advantage of the restricted expression of metabotropic glutamate receptor subtype 6 (mGluR6) in retinal ON bipolar cells, we generated knockout mice lacking mGluR6 expression. The homozygous mutant mice showed a loss of ON responses but unchanged OFF responses to light. The mutant mice displayed no obvious changes in retinal cell organization nor in the projection of optic fibers to the brain. Furthermore, the mGluR6-deficient mice showed visual behavioral responses to light stimulation as examined by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
414
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(445 citation statements)
references
References 34 publications
28
414
2
1
Order By: Relevance
“…Similar abnormalities also have been noted in mice lacking expression of bassoon (Dick et al, 2003) as well as in mice that lack functional rod or cone photoreceptors (Claes et al, 2004). In comparison, mice with mutations in the postsynaptic proteins mGluR6, nyctalopin or G α0 , do not share these morphological abnormalities (Pardue et al, 2001;Ball et al, 2003;Masu et al, 1995;Tagawa et al, 1999;Dhingra et al, 2000Dhingra et al, , 2002.…”
Section: Role Of the α 1f Subunit Of The Vdcc In Synaptic Developmentsupporting
confidence: 56%
See 2 more Smart Citations
“…Similar abnormalities also have been noted in mice lacking expression of bassoon (Dick et al, 2003) as well as in mice that lack functional rod or cone photoreceptors (Claes et al, 2004). In comparison, mice with mutations in the postsynaptic proteins mGluR6, nyctalopin or G α0 , do not share these morphological abnormalities (Pardue et al, 2001;Ball et al, 2003;Masu et al, 1995;Tagawa et al, 1999;Dhingra et al, 2000Dhingra et al, , 2002.…”
Section: Role Of the α 1f Subunit Of The Vdcc In Synaptic Developmentsupporting
confidence: 56%
“…When only synaptic transmission is compromised, the a-wave component, reflecting activity of rod and cone photoreceptors (Lamb, 1996), is spared, while the b-wave, reflecting predominantly rod or cone depolarizing bipolar cell (DBC) activity (Robson & Frishman, 1995, 1998Kofuji et al, 2000;Sharma et al, 2005), is reduced. This "negative" ERG pattern has now been reported in mice with mutations in genes encoding mGluR6 (Masu et al, 1995), nyctalopin (Pardue et al, 1998), the G-protein subunit Gα O1 (Dhingra et al, 2000(Dhingra et al, , 2002, the β 2 subunit of VDCCs (Ball et al, 2002), the presynaptic cytomatrix protein bassoon (Dick et al, 2003), or calcium-binding protein 4 (Haeseleer et al, 2004). The wide variety of proteins essential for normal synaptic transmission is suggestive of the intricacy of the synaptic complex linking photoreceptors and DBCs.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…They are also coupled to Gi/o proteins and are mostly found in the presynaptic element of many glutamatergic terminals where they negatively regulate the release process. One exception is mGlu6 which is located in the ON bipolar cells exclusively where it is responsible for most of the ON response in the retina (Masu et al, 1995). In contrast to this variety of mGluRs even further increased by the existence of various isoforms generated by alternative splicing (Pin and Duvoisin, 1995;Conn and Pin, 1997;Pin et al, 2003), only two GABA B encoding genes have been identified (Marshall et al, 1999) (Fig.1).…”
Section: Class-c Gpcrsmentioning
confidence: 99%
“…The function of mGluR6, sensitive to L-2-amino-4-phosphonobutyrate (L-AP4), is the transmission of the light signal from the photoreceptor cells to the ON bipolar cells; the photoreceptors are hyperpolarized by light, and this hyperpolarization is converted via the action of mGluR6 to a depolarization of the ON bipolar cells that convey the light ON signal to the ON ganglion cells [Masu et al (1995); for review, see Nakanishi (1995)]. …”
Section: Involvement Of Group I Mglurs In Synaptic Processing In the Oplmentioning
confidence: 99%